Sonographic Verification and Clinical Significance of the Features of Surrounding Structures in Knee Osteoarthritis - E. A. Skripnichenko; V. V. Lyalina; S. G. Pripisnova; V. G. Gоlubev (Архивъ внутренней медицины)
Background: Osteoarthritis (OA) of the knee joint is one of the most dangerous diseases, the most significant manifestation of which is chronic pain syndrome. There is a low correlation between the radiographic stage of OA and pain progression. First of all, this is a variety of pain syndromes, among which is the pathology of periarticular structures (AS). To date, the contribution of this type to the clinical picture of OA has been sufficiently studied, primarily due to the fact that the list and frequency of these lesions have not yet been described.Aim: to describe the basis of the main periarticular structures in patients with different radiographic stages of knee OA according to ultrasound data.Materials and methods: The observational study has currently included 88 patients who had an outpatient appointment with a rheumatologist for knee osteoarthritis between 2021 and 2023. The study assessed 110 knee joints using clinical and ultrasound techniques.Results: The most common periarticular ultrasound changes, regardless of radiographic stage, were pes anserine tendinopathy (57.3 %), Baker’s cyst (45.5 %), fibrosis of the severe Hoffa body (40 %) and ligamentopathy of the medial collateral ligament (36). ,4). %). A significant correlation was found between the number of changes according to ultrasound and the radiological stage (ρ=0.45 [95 % CI: 0.28, 0.59], p <0.001) as well as between the VAS and the definition of identified ultrasound changes (ρ= 0.29 [95 % CI: 0.11, p=0.002); In addition, it was shown that late stages of OA are associated with a greater content of changes (p <0.001).Conclusion: Changes in periarticular structures are present in most patients with knee osteoarthritis; their number correlates with the VAS value and radiographic stage of OA. Details of these changes, their clinical significance and pathogenetic contribution to the progression of knee OA require further study.